2021
DOI: 10.1021/acs.macromol.0c02876
|View full text |Cite
|
Sign up to set email alerts
|

Diarylfluorene Flexible Pendant Functionalization of Polystyrene for Efficient and Stable Deep-Blue Polymer Light-Emitting Diodes

Abstract: Intermolecular aggregation and phase transition are exacerbated by enhancing the free motion of small molecules in the solid state upon an external active stimulus, which is negative to the device performance and stability of deep-blue organic lightemitting diodes (OLEDs). Herein, we proposed a convenient and simple "flexible"-pendant-functionalization strategy to obtain a polystyrene (PS) derivative (PS-MC8TPA) with an excellent stable morphology and efficient deep-blue emission for polymer lightemitting diod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The results implied that FCz‐C8‐Am could be used as a light‐emitting layer for solution‐processed deep blue OLED devices, even if device efficiency is an important constraint to be overcome. In fact, our OLED exhibited a low performance compared to many previous deep‐blue PLEDs, [ 12f,27 ] but the performance was comparable to that of OLEDs based on supramolecular polymers. [ 28 ] However, this was not the optimal device efficiency, compared to the ultra‐high performance deep‐blue OLEDs reported in previous works (≈7.3 cd A −1 ).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The results implied that FCz‐C8‐Am could be used as a light‐emitting layer for solution‐processed deep blue OLED devices, even if device efficiency is an important constraint to be overcome. In fact, our OLED exhibited a low performance compared to many previous deep‐blue PLEDs, [ 12f,27 ] but the performance was comparable to that of OLEDs based on supramolecular polymers. [ 28 ] However, this was not the optimal device efficiency, compared to the ultra‐high performance deep‐blue OLEDs reported in previous works (≈7.3 cd A −1 ).…”
Section: Resultsmentioning
confidence: 72%
“…Finally, with the combination of a pendant Cz unit and conjugated backbone structure, [14,27] the optoelectrical properties of FCz-C8-Am were also investigated by fabricating preliminary OLEDs. First, because of the good film-forming ability of FCz-C8-Am, the average roughness of a spin-coated film from a fresh solution was approximately 0.3 nm, which was significantly different from that of the xerogels (Figure S16, Supporting Information).…”
Section: Ultra-deep-blue Organic Light-emitting Diode (Oleds)mentioning
confidence: 99%
“…The reason may due to the larger molecular weight of BPCPCHY and the rigid imide structure. The high T g of the BPCPCHY can improve the morphological stability in the solid state, which is beneficial to the efficient and stable deep-blue emission. Furthermore, it is also helpful for the selection of appropriate high-boiling-point solvents and annealing temperature to replace chlorobenzene solvents that can effectively avoid the use of halogen-containing solvents and reduce environmental pollution.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the triplet excitons can be harvested through upconversion via the reverse intersystem crossing (RISC) process without additional energy supplies. Hence, highly efficient CPEL could easily be obtained from the CP-OLED devices fabricated with chiral TADF emitters, and several such examples have been reported in recent years. Compared to small organic emitters, polymers can take the advantages in thermal stability, structural diversity, and device preparation. Besides, many successful studies on TADF polymers have been reported in recent years, which gave the inspiration on designing CP-TADF polymers in order to realize highly efficient CPEL. …”
Section: Introductionmentioning
confidence: 99%